2018
DOI: 10.1016/j.gie.2018.07.035
|View full text |Cite
|
Sign up to set email alerts
|

Utility of video capsule endoscopy for longitudinal monitoring of Crohn’s disease activity in the small bowel: a prospective study

Abstract: There was high correlation between CE and ileocolonoscopy scores for the assessment of mucosal disease activity over time; however, there were no correlations between endoscopic scores and clinical parameters. The use of serial CE for the assessment of small-bowel CD is feasible and valid. (Clinical trial registration number: NCT01942720.).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 40 publications
0
23
0
Order By: Relevance
“…1,2,4 Panenteric capsule endoscopy provides an efficient, patientfriendly, option for comprehensive monitoring of the small bowel and the colon without the need for additional endoscopic procedures. Several recent publications have described the use of a colonic capsule while disengaging its two-hour sleep mode (PillCam Colon Capsule 2) for the same purpose, 8,10,[18][19][20] however PillCam Crohn's capsule represents a further evolution of this technology. The major upgrade introduced in the PCCE is the completely redesigned reading system that was adjusted to facilitate and streamline the reading of CD images.…”
Section: Discussionmentioning
confidence: 99%
“…1,2,4 Panenteric capsule endoscopy provides an efficient, patientfriendly, option for comprehensive monitoring of the small bowel and the colon without the need for additional endoscopic procedures. Several recent publications have described the use of a colonic capsule while disengaging its two-hour sleep mode (PillCam Colon Capsule 2) for the same purpose, 8,10,[18][19][20] however PillCam Crohn's capsule represents a further evolution of this technology. The major upgrade introduced in the PCCE is the completely redesigned reading system that was adjusted to facilitate and streamline the reading of CD images.…”
Section: Discussionmentioning
confidence: 99%
“…Thanks to the wide implementation of SB patency tests (patency capsule or entero‐MR/CT), in recent studies, the risk of capsule retention has remarkably decreased (up to 2.5% in established Crohn's disease) . In parallel, CE assessment of disease severity and extent in the SB has emerged as a valid diagnostic target for patients with a new diagnosis of Crohn's disease, irrespective of the findings at ileocolonoscopy, and as a reliable tool for longitudinal monitoring in the era of treat‐to‐target strategies . The advent of capsule devices with a prolonged operating time has recently opened the era of pan‐intestinal CE .…”
Section: Enteroscopy: a Powerful Weapon To Solve Big Problems In The mentioning
confidence: 99%
“…155 In parallel, CE assessment of disease severity and extent in the SB has emerged as a valid diagnostic target for patients with a new diagnosis of Crohn's disease, irrespective of the findings at ileocolonoscopy, 156 and as a reliable tool for longitudinal monitoring in the era of treat-to-target strategies. [157][158][159][160][161][162] The advent of capsule devices with a prolonged operating time has recently opened the era of pan-intestinal CE. 159,162 This all-in-one and on-demand approach has a promising application in IBD 159,[162][163][164][165] where it can supposedly speed up the diagnostic work-up and decrease the need for endoscopic procedures.…”
Section: Capsule Enteroscopymentioning
confidence: 99%
“…Recently, Eminler et al 1 reported that in patients with unintentional guidewire (GW) cannulation into the main pancreatic duct (MPD) during attempted biliary cannulation, insertion of a plastic pancreatic stent significantly increased the need for needle-knife papillotomy compared with the double-guidewire technique (DGWT) for achieving deep common bile duct (CBD) cannulation.…”
Section: Pancreatic Techniques For Common Bile Duct Cannulation In Ercpmentioning
confidence: 99%
“…To the Editor: I read with great interest the study by Melmed et al 1 comparing video capsule endoscopy with ileocolonoscopy in the longitudinal monitoring of Crohn's disease activity in the small bowel. I commend the authors on their effort to better position capsule endoscopy among other smallbowel endoscopic and imaging techniques.…”
mentioning
confidence: 99%